2001
DOI: 10.2337/diabetes.50.4.851
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Accelerates Smooth Muscle Accumulation in Lesions of Atherosclerosis

Abstract: In combination with other factors, hyperglycemia may cause the accelerated progression of atherosclerosis in people with diabetes. Arterial smooth muscle cell (SMC) proliferation and accumulation contribute to formation of advanced atherosclerotic lesions. Therefore, we investigated the effects of hyperglycemia on SMC proliferation and accumulation in vivo and in isolated arteries and SMCs by taking advantage of a new porcine model of diabetes-accelerated atherosclerosis, in which diabetic animals are hypergly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
3
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(154 citation statements)
references
References 53 publications
10
137
3
1
Order By: Relevance
“…Although previous reports demonstrated increased intimal thickening after balloon injury in alloxaninduced diabetic rabbits (27) and BB Wistar diabetic rats (28), recent studies report exaggerated intimal expansion in obese Zucker rats (29) but not in rats with STZ-induced diabetes (29,30). Coupled with the observation that in some studies, high glucose failed to stimulate SMC proliferation in culture (31,32), it is currently believed that hyperglycemia per se does not stimulate intimal hyperplasia in injured vessels and that insulin resistance or hyperinsulineima is responsible for the increased propensity of human diabetic patients for restenosis. This view is further reinforced by studies (33,34) showing that although rigorous control of hyperglycemia significantly decreases the microvascular complications such as nephropathy and retinopathy, it does not affect macrovascular complications of diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Although previous reports demonstrated increased intimal thickening after balloon injury in alloxaninduced diabetic rabbits (27) and BB Wistar diabetic rats (28), recent studies report exaggerated intimal expansion in obese Zucker rats (29) but not in rats with STZ-induced diabetes (29,30). Coupled with the observation that in some studies, high glucose failed to stimulate SMC proliferation in culture (31,32), it is currently believed that hyperglycemia per se does not stimulate intimal hyperplasia in injured vessels and that insulin resistance or hyperinsulineima is responsible for the increased propensity of human diabetic patients for restenosis. This view is further reinforced by studies (33,34) showing that although rigorous control of hyperglycemia significantly decreases the microvascular complications such as nephropathy and retinopathy, it does not affect macrovascular complications of diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is well established that subculture of the aortic smooth muscle cells reduces protein kinase G levels after a few subcultures, thus necessitating the use of primary or early subculture cells. 35 (2) Neointimal cells that are generated in vascular disease manifest a partially dedifferen- . Dominant-negative PTP1B mutant, C215S-PTP1B, blocks the capacity of NO donor SNAP to decrease insulinstimulated Erk phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is based on recent studies indicating that neointimal enlargement may be dependent on elevated insulin rather than elevated glucose levels. 2,3 Interestingly, one of these studies 3 found that hyperinsulinemia without diabetes also resulted in enhanced neointima formation after vascular injury, a finding that underscores the pivotal role of elevated insulin as a vascular pathogen. Other studies have reported that diabetes may be associated with NO deficiency, 16 a finding that could explain the tendency of insulin to enhance neointimal formation in vascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies examining the proliferative response of medial and intimal cells in carotid arteries after balloon injury in rat models of type 1 and type 2 diabetes showed increased cell proliferation in type 2 diabetic obese Zucker rats, but not in streptozotocin-induced type 1 diabetic rats [15]. In a porcine model of diabetes-accelerated atherosclerosis, diabetes was shown to accelerate smooth muscle cell accumulation in atherosclerotic lesions, but glucose treatment did not have direct growth-promoting effects [16]. These data suggest that hyperglycaemia alone does not stimulate arterial cell proliferation.…”
Section: Introductionmentioning
confidence: 95%